2017
DOI: 10.1038/s41535-017-0028-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetooptical determination of a topological index

Abstract: When a Dirac fermion system acquires an energy-gap, it is said to have either trivial (positive energy-gap) or non-trivial (negative energy-gap) topology, depending on the parity ordering of its conduction and valence bands. The non-trivial regime is identified by the presence of topological surface or edge-states dispersing in the energy gap of the bulk and is attributed a non-zero topological index. In this work, we show that such topological indices can be determined experimentally via an accurate measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 67 publications
2
35
0
Order By: Relevance
“…We have shown that the LL in IV-IV TCIs can be well described by a massive Dirac spectrum that includes spin-splitting [24] [29] [30] [31], resulting from a 6-band k.p Hamiltonian. [30] If the contributions from the far-bands are neglected a 2-band k.p Hamiltonian results, the solution of which is an ideal massive Dirac model [32].…”
Section: Fig 2 (Color Online) (A)mentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that the LL in IV-IV TCIs can be well described by a massive Dirac spectrum that includes spin-splitting [24] [29] [30] [31], resulting from a 6-band k.p Hamiltonian. [30] If the contributions from the far-bands are neglected a 2-band k.p Hamiltonian results, the solution of which is an ideal massive Dirac model [32].…”
Section: Fig 2 (Color Online) (A)mentioning
confidence: 99%
“…We also note that the SdH results nicely agree with our previous magnetooptical measurements on the same samples. [24] Even though the two samples studied here in detail have different carrier type, the other samples examined in Fig.1(c) rule out any link between this and the NLMR. [20] In x=0.19, BQL is close to the onset of the NLMR seen in Fig.2(a).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Magnetooptical Landau-level spectroscopy measurements are performed on high-quality [111]oriented Pb1-xSnxSe epilayers grown by molecular beam epitaxy as described in our previous work. [11] [26] Two 2-μm thick samples with composition x=0.19 and x=0.14, respectively above and below the topological phase transition at 4.2K, are studied. Magnetospectroscopy is performed in transmission mode in the Faraday geometry versus magnetic field and temperature.…”
mentioning
confidence: 99%